Про Кышей: [повесть-сказка] / Мила Блинова - Блинова Мила (Очень прикольная книга, 2010)
Экземпляры: М/а ДБ (20130320) / Инвентарный номер: 99524 / Цена: 120 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 69 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6